Analysis of factors associated with the selection of contraceptive methods among birth control acceptors in bandung regency - Lina Haryani; Sophia; Julina Maudy (Institute of Computer Science (IOCS), 2023)
Population growth in Indonesia in the last 10 years has increased quite rapidly by 1.25 percent per year. In Indonesia, the majority of new family planning participants are dominated by family planning participants who use Non-Long-Term Contraceptive Methods amounting to 79.48% of all new family planning participants, while those using Long-Term Contraception Methods are only 20.51%. In this study there are only 2.8% of Non-Long-Term Contraceptive Methods users compared to 97.2% of Long-Term Contraception Methods users. The purpose of the study was to determine the relationship between knowledge, education, husband's support, parity, occupation, age and sources of information in the selection of contraceptive methods. The study was conducted on June 20 – July 20, 2022. The design of this study was descriptive correlational with a cross-sectional approach. The research sample was taken from 66 respondents from family planning acceptors using quota sampling technique. Univariate and bivariate analysis were performed with chi-squarepp statistical test. The results of the analysis showed that there was a relationship between the choice of contraceptive method, namely education (p=0.03), parity (p=0023), husband's support (p=0.031), occupation (p=0.046), age (p=0.015), sources of information (p = 0.022), which is not related is knowledge (p value = 0.068). It is recommended that midwives can provide better information, improve contraceptive services, especially long-term contraceptive methods.